COSEISMIC AND POSTSEISMIC SLIP OF THE 2004 PARKFIELD EARTHQUAKE FROM SPACE-GEODETIC DATA - Johanson I.A.; Bürgmann R.; Fielding E.J.; Rolandone F. (My University, 2006)
We invert interferometric synthetic aperture radar (InSAR) data jointly with campaign and continuous global positioning system (GPS) data for slip in the coseismic and postseismic periods of the 2004 Parkfield earthquake. The InSAR dataset consists of eight interferograms from data collected by the Envisat and Radarsat satellites spanning the time of the earthquake and variable amounts of the postseismic period. The two datasets complement each other, with the InSAR providing dense sampling of motion in the range direction of the satellite and the GPS providing more sparse, but three-dimensional measurements of ground motion. The model assumes exponential decay of the postseismic slip with a decay time constant of 0.087 years, determined from time series modeling of continuous GPS and creepmeter data. We find a geodetic moment magnitude of M 6.2 for a 1-day coseismic model and Mw 6.1 for the entire postseismic period. The coseismic rupture occurred mainly in two slip asperities; one near the hypocenter and the other 15-20 km north. Postseismic slip occurred on the shallow portions of the fault and near the rupture areas of two M 5.0 aftershocks. A comparison of the geodetic slip models with seismic moment estimates suggests that the coseismic moment release of the Parkfield earthquake is as little as 25% of the total. This underlines the importance of aseismic slip in the slip budget for the Parkfield segment.